THU0288 Survival of Methotrexate in Patients with Giant Cell Arteritis: A 22-Years Follow-Up Cohort. (9th June 2015) - Artietti Lopez, L.; Gόmez, A.; Rosales Rosado, Z.; Freites, D.; Morado Quiñoa, I.; Lajas, C.; Fernández, B.; Abásolo Alcázar, L.
Abstract : Background: Having demonstrated the safety and efficacy of Methotrexate (MTX) in the treatment of Giant Cell Arteritis (GCA), it is important to know the long-term survival of the drug in these patients. Objectives: To describe the incidence of discontinuation of MTX and its causes in a cohort of patients with GCA. Methods: Retrospective longitudinal observational study of 22 years of follow-up. Subjects: Patients treated in the Department of Rheumatology of the Hospital Clínico San Carlos, Madrid, from January 1991 until September 2014, diagnosed (according to ICD 10) ACG and treated with MTX. Primary endpoint: discontinuation of MTX due to: inefficiency; adverse event (AE) (moderate: discontinuation of the drug regardless the impact; severe: discontinuation and hospitalization or death); patient choice; improvement or remission; and other decisions of the physician. Secondary endpoints: a) sociodemographic (age, sex); b) clinical: baseline comorbidity; c) erythrocyte sedimentation rate; d) characteristics of the arteritis outbreak; e) cumulative dose of corticosteroids during the first 3 months. Statistical analysis: Description of sociodemographic and clinical characteristics of patients included and of discontinuation causes, through frequency distribution, and mean and standard deviation or median and percentiles. To estimate MTX discontinuation rates, survival techniques were used, incidence is expressed per 100 patients * year with their respective 95% confidence interval (95% CI). Results: Eighty two GCA patients were included in the study, the same received 96 courses of treatment, with a total follow-up of 168.3 patient * year. From these patients, 75.61% were women with a mean age at diagnosis of 76.7±7.3 years. At diagnosis, 58.5% of patients were hypertensive, and 22% diabetics. Temporal artery biopsy was performed in 92% of patients and it was positive in 72%. The mean sedimentation rate was 84.6±28.1 mm/h and the cumulative dose of corticosteroids in the first 3 months was 32.3±11.8 mgr. The most common clinical was headache (87%), abnormal temporal artery (46%), jaw claudication (44%), associated polymyalgia rheumatica (PMR) (42%), and asthenia (40%). Sixty three discontinuations (65%) were recorded: 57% by AE (infections were the most common cause (58%); 32% due to improvement or remission; 5% due to inefficiency; 3% due to patient decision and 3% due to decision of the physician. In 9.3% of patients, follow-up was lost and 3 patients died (one related to taking MTX). MTX survival in the first year was 70%, 50% in the second year and it was 18% at year 5. The incidence of suspension of MTX was 37.4 (95% CI 29.2 to 47.9), with an incidence of 34.9 (95% CI 26.3 to 46.3) in women and 48.5 (IC 95% CI 29.2 to 80.4) in men. If we stratify patients into three categories (<75 years, 75-85 years and>85 years), the incidence of discontinuation increases with age. In the table, MTX discontinuation rates are shown by cause. Conclusions: Discontinuation rate estimated in our cohort is of 37% patients * year, being the most frequent cause the AE (primarily infections), followed by improvement or remission. This study contributes to increasing knowledge of long-term survival of MTX in patients with GCA in real life conditions Disclosure of Interest: None declared